Child Labor's Experience of Communication Behavior - Diniati, Anisa; Suryana, Asep; Bajari, Atwar (Jurnal Komunikasi, 2022)
Life as child labor is a compulsion that must be accepted for certain reasons. Some of the reasons why children in the Cibaduyut shoe industry center work as child laborers, including the living environment, which is indeed a home industry area, work that has been passed down from parents to children, to unmet needs from the family so that children have to look for jobs. own money to meet their needs. The purpose of this study is to analyze the experiences of child laborers regarding their communication behavior. The theory that underlies this research is the Phenomenological theory of Viktor Frankl, and the Symbolic Interaction theory of Mead. This study uses a qualitative approach with phenomenology as the research method. The results showed that the experience of child laborers regarding communication behavior is closely related to communication in shoe repair shops with bosses and employers, adult co-workers and fellow child laborers, peer groups, and family members. The communication of child laborers with the four environments encourages them to create distinctive cultural characteristics in the form of a world of symbols created together. The suffering they face is interpreted differently by child laborers, so that child laborers do not carry out the process of movements to lead to a better life.